2022
DOI: 10.14740/jmc4000
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol 3350 Crystal Nephropathy in Association With Glomerular Mesangial Immunoglobin A Deposition

Abstract: Polyethylene glycol (PEG) 3350, an active ingredient of over-thecounter MiraLAX, is a commonly used laxative in children and is produced by polymerization of ethylene glycol (EG). Masked EG toxicity secondary to contamination of PEG 3350 could occur. We present a 7-year-old child with developmental delay who presented with altered mental status and acute kidney injury (AKI) following intake of generic PEG 3350 for few days prior to presentation. There was high anion gap metabolic acidosis, hypernatremia, eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…22) Ergocalciferol contains 103.6 g/100 mL of PG, and 600,000 IU is equivalent to 75 mL of the solution or 77.7 g of PG. Another study by Aly et al 20) revealed that an EG-contaminated laxative was the primary cause of AKI in a boy with a complicated congenital disease. Based on the renal biopsy evaluation, the drugs were suspected to be contaminated with EG.…”
Section: Contribution Of Other Contaminated Drugs To Unexplained Akimentioning
confidence: 98%
See 3 more Smart Citations
“…22) Ergocalciferol contains 103.6 g/100 mL of PG, and 600,000 IU is equivalent to 75 mL of the solution or 77.7 g of PG. Another study by Aly et al 20) revealed that an EG-contaminated laxative was the primary cause of AKI in a boy with a complicated congenital disease. Based on the renal biopsy evaluation, the drugs were suspected to be contaminated with EG.…”
Section: Contribution Of Other Contaminated Drugs To Unexplained Akimentioning
confidence: 98%
“…13) Most studies have been case reports of a single patient with DEG-induced unexplained AKI. 7,[20][21][22][23][24][25][26][27][28][29] Some case reports described unintentional EG contamination or DEG-induced oliguria or anuria 21,24,27,29) after the consumption of a DEG-contaminated acetaminophen elixir, 26) PG-containing intravenous phenobarbital and pentobarbital for uncontrolled seizures, 28) DEG ingestion suicide attempts, 7) ergocalciferol-containing high-dose vitamin D dissolved in PG for diagnosing nutritional rickets, 22) intentional EG poisoning in baby formula, 25) DEG-contaminated fever and cough medication, 23) and EG contamination of laxatives. 20) High-quality studies of AKI induced by DEG and other glycol-induced AKI are limited.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 2 more Smart Citations